The American tradition in José Martí between philosophy and literature - Pampín, María Fernanda (Anales de Literatura Hispanoamericana, 2017)
Cultural relationships between Cuba and the United States have been very productive since the Nineteenth Century. Without hesitation, the proximity of Cuba to the great North Country has been a core generator of senses. According to these issues, this paper proposes tracing Marti interest in American philosophy and literature, a neglected aspect by classical Latino Americanism. In this sense, it plans to relocate the work of Martí in the center of nineteenth-century Western canon, establishing a dialogue between Ralph Emerson, Walt Whitman and Martí. This dialogue allows exploring, complicating and reconsidering the weight that had Anglo-Saxon tradition in the construction of Marti’s literature and thought.